A Review of the electrochemical corrosion of metals in choline chloride based deep eutectic solvents - Mihael Bučko (International Association of Physical Chemists (IAPC), 2021)
Deep eutectic solvents (DESs) are a class of mixtures with melting points notably lower than those of their raw constituent components. These liquids have found a tremendously wide spectrum of applications in the last two decades of their research, so their contact and interaction with technical metals and alloys are inevitable. Therefore, the corrosivity of DESs towards metals is an extremely important topic. This review summarizes research efforts collected in the last two decades related to the corrosion rate of various metals in different DESs. Since the DESs are mainly composed of organic raw compounds, and by their physicochemical properties they may be regarded as a separate class of ionic liquids, the literature data about DESs corrosivity has been compared to the data related to the corrosivity of various organic solvents and ionic liquids as well. All the results gained until now show significantly low corrosivity of DESs. This observation is discussed in relation to the chemical composition of DESs. The absence of the oxidizing agents, the inhibitory action of organic ions and molecules, high viscosity and low electrical conductivity have been recognized as the main factors contributing to the low metal corrosion rate in DESs.